Outcomes of Patients With Metastatic Differentiated Thyroid Cancer After Excellent Response to Treatment - Hsu, Chia-Jung; Lai, Kun-Yu; Lu, Yu-Ling; Wu, Ming-Hsien; Liu, Feng-Hsuan; Lin, Shu-Fu (Frontiers in Endocrinology, 2022)
Background: To evaluate the outcomes in differentiated thyroid cancer (DTC) patients who achieved excellent response to initial treatment and developed distant metastasis during follow-up. Methods: Thyroid cancer patients registered in Chang Gung Memorial Hospital thyroid cancer database between January 1979 and December 2019 were assessed. Results: Among 1053 DTC patients with excellent response to initial therapy, 14 (1.3%) patients developed metastatic disease during follow-up, including 6 males and 8 females with median age of 50.2 years [interquartile range (IQR), 39.9-53.7]. Nine (64.3%) patients had papillary cancer, four (28.6%) had follicular cancer, and one (7.1%) had Hürthle cell cancer. Most patients (92.9%) had stage I disease at diagnosis. The sites of metastasis were lung (71.4%), bone (7.1%), mediastinum (7.1%) and multiple sites (14.3%). With a median follow-up of 18.3 years (IQR, 14.8-23.8), 2 patients had disease-specific mortality. The 5- and 10-year disease-specific survival after the diagnosis of distant metastasis was 92% and 74%, respectively. Multiple sites of metastasis was associated with increased risk of mortality (P = 0.022). Conclusions: A small proportion of DTC patients with an excellence response to initial therapy developed distant metastasis during follow-up. Multiple organ distant metastases conferred a worse disease-specific survival.